2021
DOI: 10.1186/s42523-021-00079-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of the bovine ocular bacterial community dynamics in calves

Abstract: Background Infectious Bovine Keratoconjunctivitis (IBK), commonly known as pinkeye, is one of the most significant diseases of beef cattle. As such, IBK costs the US beef industry at least 150 million annually. However, strategies to prevent IBK are limited, with most cases resulting in treatment with antibiotics once the disease has developed. Longitudinal studies evaluating establishment of the ocular microbiota may identify critical risk periods for IBK outbreaks or changes in the microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…This indicates that these core taxa can colonize and inhabit the respiratory, gastrointestinal and reproductive tracts regardless of the drastic differences in physiological conditions in these locations. The majority (80%) of these core taxa are members of the Firmicutes , which is one of the most ubiquitous and relatively abundant bacterial phyla in the respiratory, gastrointestinal and reproductive tract- (vagina, uterus) (Galvão et al, 2019), mammary gland- (Derakhshani et al, 2018), ocular- (Bartenslager et al, 2021) and hoof- (Zinicola et al, 2015) -associated microbiota in cattle, demonstrating the adaptability of members of this phylum. Nine taxa within the Actinobacteria phylum including Bifidobacterium pseudolongum and several Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that these core taxa can colonize and inhabit the respiratory, gastrointestinal and reproductive tracts regardless of the drastic differences in physiological conditions in these locations. The majority (80%) of these core taxa are members of the Firmicutes , which is one of the most ubiquitous and relatively abundant bacterial phyla in the respiratory, gastrointestinal and reproductive tract- (vagina, uterus) (Galvão et al, 2019), mammary gland- (Derakhshani et al, 2018), ocular- (Bartenslager et al, 2021) and hoof- (Zinicola et al, 2015) -associated microbiota in cattle, demonstrating the adaptability of members of this phylum. Nine taxa within the Actinobacteria phylum including Bifidobacterium pseudolongum and several Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that these core taxa can colonize and inhabit the respiratory, gastrointestinal and reproductive tracts regardless of the drastic differences in physiological conditions in these locations. The majority (80%) of these core taxa are members of the Firmicutes, which is one of the most ubiquitous and relatively abundant bacterial phyla in the respiratory, gastrointestinal and reproductive tract-(vagina, uterus) [3], mammary gland- [67], ocular- [68] and hoof- [69] -associated microbiota in cattle, demonstrating the adaptability of members of this phylum. Nine taxa within the Actinobacteria phylum including Bifidobacterium pseudolongum and several Corynebacterium spp.…”
Section: Holistic View Of Microbial Communities Across Respiratory Gastrointestinal and Reproductivementioning
confidence: 99%
“…were associated with group I ( P <0.05) and, therefore, had less participation in KC, especially in group III. Bartenslager et al [33] evaluates the presence of Moraxella and Mycoplasma in 19 calves with KC at four time points, and observed that Moraxella spp. were identified in all time points, particularly in the first period.…”
Section: Discussionmentioning
confidence: 99%